Review of the diagnosis of production water treatment in Colombian petroleum fields - Ortega Ramírez, Angie Tatiana; Arcila, Yurleni Fernanda; Vargas Díaz, Laura Marcela (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2021)
This article aims to study the methods of water resource management in the petroleum industry. This research looks for scientific information obtained in databases such as Scopus, Science Direct, or Redalyc, and inquiries extracted from government reports, Colombian legislation, and operations of companies belonging to the hydrocarbon sector such as Ecopetrol or Pacific, among others, are reviewed. With the data, conventional and non-conventional methods of separation between water and crude petroleum are classified. Finally, three uses given to the produced water in Colombia are highlighted: injection, surface discharge, and adaptation as irrigation water in agricultural activities.